Urgensi Penghormatan Otonomi dan Hak Menerima Informasi Vaksinasi Covid-19 dalam Konteks Kewajiban Vaksinasi - Ervin Dyah Ayu Masita Dewi (Jurnal HAM, 2022)
Currently, the Covid-19 vaccination coverage is quite high, reaching 62%. Ironically, there are many rejection and inappropriate motivation in receiving vaccines. Enthusiasm for vaccination didn't represent the understanding regarding vaccination. Lack of understanding can be caused by limited or ineffective information. To describe the provision of information during the Covid-19 vaccination, a descriptive qualitative study was conducted with in-depth interviews with ten respondents. The data was analyzed by making coding and themes and compared with references. The results showed that four out of ten respondents didn't receive information prior to the Covid-19 vaccination. It was also found that the motivation to receive vaccines was only as an obligation and for using public facilities. On the other hand, vaccinators had limitations in providing information and only prioritize vaccination coverage. Without adequate information, receiving vaccine would be a mere compulsion. Respect for autonomy of vaccine recipients and rights to receive information as parts of human rights didn't work. The obligation to receive the Covid-19 vaccination in the context of a pandemic must respect the rights and autonomy of the community. Collaboration from the government and local leaders and structured coordination are needed so that the Covid-19 vaccination is accordance with ethical standards.